PENGARUH RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN JASA SUB SEKTOR RESTORAN, HOTEL & PARIWISATA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Salsabyla Azky; Embun Suryani; Nur Aida Arifah Tara (Master of Management, Mataram University, 2021)
This research aims to analysis the influence of profitability ratios proxied by Return On Assets (ROA), leverage ratios proxied by Debt to Asset Ratio (DAR), liquidity ratios proxied by Current Ratio (CR) and activity ratios proxied by Total Asset Turnover (TATO) on the prediction of financial distress on service companies of hotel, restaurant and tourism sub-sector listed on the Indonesia Stock Exchange period of 2015-2019. The criteria of financial distress in research were measured using the Interest Coverage Ratio (ICR) with a value criterion of less than one. Analysis method used in this research is logistic regression. The research results show that the profitability ratio had an effect on the prediction of financial distress. While the leverage ratio, liquidity ratio and activity ratio have no effect on the prediction of financial distress. Keywords: Financial Distress, ROA, DAR, CR, TATO, ICR